Association between personality traits, eating behaviors, and the genetic polymorphisms FTO-rs9939609 and MAO-A 30 bp u-VNTR with obesity in Mexican Mayan children - Vázquez-Pérez, Luis Alberto; Hattori-Hara, Mónica; Arankowsky-Sandoval, Gloria; Pérez-Mendoza, Gerardo; Rubi-Castellanos, Rodrigo; Rangel-Méndez, Jorge Aarón; Pinto-Escalante, Doris; Canto-Cetina, Thelma; González-Herrera, Lizbeth (Frontiers in Genetics, 2024)
Introduction: Genetic variants that control dopamine have been associated with obesity in children through loss of control of satiety and impulses, the manifestation of addictive eating behaviors, and specific personality traits. The variants include FTO-rs9939609 and the MAO-A 30 pb u-VNTR low-transcription alleles (LTA). Objective: To evaluate the genetic association of FTO-rs9939609 and the MAO-A LTA, along with personality traits and eating behavior with obesity in Mayan children from Mexico. Methods: We crosssectionally evaluated 186 children (70 with obesity and 116 with normal weight) 6-12 years old from Yucatan, Mexico. Nutritional status was defined with body mass index (BMI) percentiles. Personality traits were evaluated with the Conners and TMCQ tests; eating behavior was evaluated with the CEBQ test. Genotyping with real-time PCR and TaqMan probes was used for FTO-rs9939609, whereas PCR amplification was used for MAO-A u-VNTR. Results: High-intensity pleasure (p = 0.013) and moderate appetite (p = 0.032)differed according to nutritional status. Heterozygous FTO-rs9939609 T/A children showed higher mean scores of low-intensity pleasure (p = 0.002) and moderate appetite (p = 0.027) than homozygous T/T. Hemizygous boys having MAO-A LTA showed significantly higher mean scores of anxiety (p = 0.001) and impulsivity (p = 0.008). In multivariate models, only LTA alleles of MAO-A explained obesity in boys (OR= 4.44;.In the present study, MAO-A u-VNTR alleles were associated with obesity in multivariate models only in boys. These alleles might also have a role in personality traits such as anxiety and impulsivity, which secondly contribute to developing obesity in Mayan boys.